Pablo and the miracle of Saint Anton - Hansen-Cole, Robin (Mahwah, N.J. : Paulist Press, 1990)
Pablo, his dog, and his donkey experience the Feast of Saint Anton in a totally different way than they expected.
Keywords: Anthony, -- of Egypt, Saint, -- ca. 250-355 or 6 -- Juvenile fiction; Anthony, -- of Egypt, Saint, -- ca. 250-355 or 6 -- Fiction; Donkeys -- Fiction; Dogs -- Fiction; Spain -- Fiction